2010
DOI: 10.1542/peds.2008-3211
|View full text |Cite
|
Sign up to set email alerts
|

Mild Controlled Hypothermia in Preterm Neonates With Advanced Necrotizing Enterocolitis

Abstract: Mild hypothermia for 48 hours in preterm neonates with severe NEC seems both feasible and safe. Additional investigation of the efficacy of this therapeutic intervention in this population is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 28 publications
1
42
0
2
Order By: Relevance
“…In a nonrandomized feasibility trial, Hall et al administered therapeutic hypothermia to 15 infants with advanced NEC and multiorgan dysfunction. 128 Median gestation at birth of babies in this trial was 27 weeks, with a median admission weight of 1.1 kg. All infants received hypothermia for 48 hours.…”
Section: Therapeutic Hypothermia For Necmentioning
confidence: 88%
“…In a nonrandomized feasibility trial, Hall et al administered therapeutic hypothermia to 15 infants with advanced NEC and multiorgan dysfunction. 128 Median gestation at birth of babies in this trial was 27 weeks, with a median admission weight of 1.1 kg. All infants received hypothermia for 48 hours.…”
Section: Therapeutic Hypothermia For Necmentioning
confidence: 88%
“…On the other hand, induced hypothermia in sick premature infants might have deleterious effects. In this regard, Hall et al [27] showed that induced hypothermia in preterm infants with severe necrotizing enterocolitis significantly impaired all parameters of blood clot dynamics. In addition, Zayek and Eyal [28] showed that hypothermia !…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are activated by either epinephrine or ADP, and the time required for the aperture to close, through adhesion and aggregation of platelets, is reported as the closure time [9] . Other means of quantifying platelet function, not used in the present report, include thromboelastography as employed by Hall et al [10] studying cooling in preterm neonates with advanced necrotizing enterocolitis. Supplementing our measurements with this method might have added useful information to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for instituting hypothermia were those suggested by the manufacturer [10] . Also included were an Apgar score ^ 5 at 10 min or a continued need for resuscitation 10 min after birth, or pH !…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation